The Effects of Virtual Museums on Students’ Positive Interdependence in learning Italian as a Foreign Language - Compagnoni, Ilaria (Babylonia (Asssociation Babylonia Suisse), 2022)
Evidence suggests that positive interdependence is the foundation of language learning and task-based interactions, linking museums to educational institutions in fostering visitor communication with artwork through Foreign Language (FL) use. Despite the increasing adoption of digital resources in education, little research has yet been devoted to the effects of virtual museums on language students’ positive interdependence. This paper discusses the results of interventions conducted on 15 students of Italian as a FL with the digital collection of Palazzo Ducale in Venice. By assessing their impact on learners’ interactions, virtual museums are shown to increase positive interdependence through cooperation, turn-taking, negotiation and role-assignment during task-based language activities.